Interactive Learning Interfaces to Enhance Student Engagement and Performance in the Government Education Sector of Higher Schools of Punjab - Arqam Tariq; Muhammad Waseem Iqbal; Hinna Hafeez; ZaibunNisa (Journal of Public Policy Practitioners, 2023)
Punjab is Pakistan's largest province and according to the School Census of Punjab, there are around 12.86 million students enrolled in public schools, and there are 391,799 teachers working in 52,470 public schools, resulting in a 33:1 student-teacher ratio. Pakistan as a whole and Punjab province both have literacy rates of above 70%, yet this is not a real reflection of Pakistan's educational system. Punjab’s current educational policy has major flaws, including high student-teacher ratio, uneven distribution of teachers with scarcity in rural regions, deteriorating educational outcomes, a declining proportion of children who attend government schools, declining proportion of public-school graduates working in white-collar jobs, increasing number of out-of-school children (“Punjab Province”, 2018), and many others. Pakistan needs to enhance its public education system not only to tackle economic, social, and developmental challenges but also to meet international commitments like the Sustainable Development Goals (SDGs). The digital revolution, driven by technological advancements, has transformed various industries, including education. This shift allows the adoption of Learning Management Systems (LMS) in higher education institutions within Punjab's government education system. By replacing traditional textbooks with digital content and utilizing interactive learning interfaces, policymakers and educators can create a more effective and engaging learning environment. The study's implications extend beyond Punjab, serving as a valuable guide for similar programs globally aiming to enhance student performance and engagement in government schools.